Evaluation of decision-to-delivery interval in emergency cesarean section: A 1-year prospective audit in a tertiary care hospital - Sunanda Gupta; Udita Naithani; C Madhanmohan; Ajay Singh; Pradeep Reddy; Apoorva Gupta (Wolters Kluwer Medknow Publications, 2017)
Background and Aims: The American College of Obstetricians and Gynecologists (ACOG) committee on professional standards and the National Institute of Clinical Excellence (NICE) guidelines suggest that decision-to-delivery interval (DDI) and emergency cesarean section (CS) should not be more than 30 min, and a delay of more than75 min in the presence of maternal or fetal compromise can lead to poor outcome. This prospective 1-year study was conducted on emergency CS in a tertiary care hospital to evaluate the DDI, factors affecting it and to analyze their effects on maternal and neonatal outcome. Material and Methods: A structured proforma was used to analyze the data from all women undergoing emergency CS, during a 1-year period, included in Category 1 and 2 of NICE guidelines for CS. Results: A total of 453 emergency CSs were evaluated, with a mean DDI of 36.3 ± 17.2 min for Category 1 CS and 38.1 ± 17.7 min for Category 2 CS (P > 0.05). Only 42.4% emergency CSs confirmed to the 30 min DDI while 57.6% had a DDI of more than 30 min. Reasons of delay were identified as a delay in shifting the patient to operation theater (22.1%), anesthesia factors (18.1%), and lack of resources or manpower (16.1%). Maternal complications occurred in 15 (3.3%) patients with 3 (0.7%) nonsurvivors having a DDI of 91.0 ± 97.0 min as compared to survivors with a DDI of 36.8 ± 15.7 min, P = 0.001. There was no significant association between DDI and occurrence of neonatal complications. Conclusion: Failure to meet the current recommendations was associated with adverse maternal outcomes, but not with adverse neonatal outcome.